From high peaks to deep valleys: Using a situation- and person-oriented approach to assess within- and between-student variation in momentary engagement and disengagement. (December 2022) - Järvinen, Jussi; Ketonen, Elina E.; Hietajärvi, Lauri; Salmela-Aro, Katariina
Abstract: The present study investigated the qualitatively different moments of engagement and disengagement experienced by students at upper-secondary school in academic situations. Further, we examined between-student differences in the occurrence of these moments and their associations with both momentary task performance and overall academic achievement. By means of multilevel latent profile analysis (MLPA) we examined 1392 momentary experiences of 130 students, collected via experience sampling method (ESM). We identified six types of (dis)engagement moments varying within students from moment to moment: high engagement, moderate engagement, indifferent engagement, anxious engagement, anxious disengagement and bored disengagement. In addition, we identified four student profiles: highly engaged, moderately engaged, indifferently engaged and anxious. Whereas the engagement moments were related to momentary task performance, there were no differences between the student profiles in academic achievement. These results shed light on the nuanced nature of engagement and disengagement, and how they vary across individuals and situations. Highlights: The study uses experience sampling data and intraindividual latent profile analysis. Six momentary profiles and four student profiles were found. Students experience aspects of engagement and disengagement simultaneously. Students reported higher task performance during highly engaging moments.